A Comparison of Internal, Marginal, and Incisal Gaps in Zirconia Laminates Fabricated Using Subtractive Manufacturing and 3D Printing Methods - Mijun Noh; Jaehong Kim (Biomimetics)
DLP printing is a new method for producing zirconia laminates that ensure clinically acceptable gaps in the internal, marginal, and incisal regions. A typical model of a central maxillary incisor was prepped by a dentist and scanned. The laminate was designed using CAD software version 2023. The laminates were fabricated using a milling machine (LSM group) and a DLP printer (LAM group) (N = 20). The gap was evaluated using the silicone replica method at designated measurement points. Statistical analyses were performed. The Shapiro–Wilk and Kolmogorov–Smirnov tests indicated a non-normal distribution, and the Mann–Whitney test was used. The LSM group had wider gaps than the LAM group except at point E (59.5 µm). The LAM group had wider gaps than the LSM group, except at points H (51.70 µm). No significant differences were observed between the LSM and LAM groups at any of the labiolingual measurement points. In the mesiodistal plane, a significant difference was observed between the two groups at point G, which was adjacent to the mesial side (p < 0.05). The results of this study indicate that DLP printing offers an innovative approach for producing zirconia laminates, as the incisal, internal, and marginal gaps are within clinically acceptable ranges compared with the AM method.